MRI data-driven clustering reveals different subtypes of Dementia with Lewy bodies - Inguanzo, Anna; Poulakis, Konstantinos; Mohanty, Rosaleena; Schwarz, Christopher G; Przybelski, Scott A; Diaz-Galvan, Patricia; Lowe, Val J; Boeve, Bradley F; Lemstra, Afina W; van de Beek, Marleen; van der Flier, Wiesje; Barkhof, Frederik; et al. (NPJ Parkinson's disease, 2023)
Dementia with Lewy bodies (DLB) is a neurodegenerative disorder with a wide heterogeneity of symptoms, which suggests the existence of different subtypes. We used data-driven analysis of magnetic resonance imaging (MRI) data to investigate DLB subtypes. We included 165 DLB from the Mayo Clinic and 3 centers from the European DLB consortium and performed a hierarchical cluster analysis to identify subtypes based on gray matter (GM) volumes. To characterize the subtypes, we used demographic and clinical data, as well as β-amyloid, tau, and cerebrovascular biomarkers at baseline, and cognitive decline over three years. We identified 3 subtypes: an older subtype with reduced cortical GM volumes, worse cognition, and faster cognitive decline (n = 49, 30%); a subtype with low GM volumes in fronto-occipital regions (n = 76, 46%); and a subtype of younger patients with the highest cortical GM volumes, proportionally lower GM volumes in basal ganglia and the highest frequency of cognitive fluctuations (n = 40, 24%). This study shows the existence of MRI subtypes in DLB, which may have implications for clinical workout, research, and therapeutic decisions.